Re-emergent Tongue Tremor as the Presenting Symptom of Parkinson’s Disease - Delil, Şakir (Balkan Med J, 2015)
BACKGROUND: The most common symptom of Parkinson’s disease is the unilateral, typically resting tremor in body parts, most commonly in the upper extremities. However, this finding can spread to the other parts of the body like lips, chin, jaw and tongue during the course of the disease. Nevertheless, we have not come across any Parkinson’s disease case presenting with tongue tremor in the literature. CASE REPORT: Here, we present a 58 year-old man with Parkinson’s disease presenting with tongue tremor, his striking response to the levodopa test and his follow-up data. CONCLUSION: The topography of motor symptoms at onset in Parkinson’s disease is presumably determined by the severity of the Lewy body neuronal degeneration in distinct parts of the substantia nigra. Therefore, patterns of somatic symptom progression in Parkinson’s disease indicate that involvement of the cranial structures always follows the development of symptoms in the extremities. However, in our case, cranial structures seem to precede the involvement of extremity-related areas.